Avoiding scar tissue formation of peripheral nerves with the help of an acellular collagen matrix - Aman, Martin; Mayrhofer-Schmid, Maximilian; Schwarz, Daniel; Bendszus, Martin; Däschler, Simeon C.; Klemm, Tess; Kneser, Ulrich; Harhaus-Wähner, Leila; Böcker, Arne Hendrik (PLOS ONE, 2023)
Extensive scar tissue formation after peripheral nerve injury or surgery is a common problem. To avoid perineural scarring, implanting a mechanical barrier protecting the nerve from inflammation processes in the perineural environment has shown promising results for functional recovery. This study investigates the potential of an acellular collagen-elastin matrix wrapped around a peripheral nerve after induction of scar tissue formation.